Chatbots in Pharmacy: A Boon or a Bane for Patient Care and Pharmacy Practice? (Sciences of Pharmacy, 2023)
Chatbots in pharmacies have gained popularity in recent years, potentially revolutionizing patient care and pharmacist workflow. However, whether chatbots are, a boon or a bane for the pharmacy profession remains. This review article aims to comprehensively analyze the literature on chatbots in pharmacy, including their benefits, limitations, and future directions. Findings suggest that chatbots have the potential to improve medication adherence, provide patient education, and streamline pharmacist workflow. However, there are limitations to their use, such as the need for robust natural language processing algorithms and concerns regarding patient privacy and security. Furthermore, the lack of regulatory oversight and standardized development processes may hinder their widespread adoption. Overall, while chatbots have the potential to improve certain aspects of pharmacy practice, caution must be taken to ensure their accuracy and safety. Moreover, chatbots should be viewed as a tool to support pharmacists in providing high-quality patient care rather than replacing the valuable expertise and human connection pharmacists provide. Further research is needed to explore the full potential of chatbots in pharmacy practice and to address the limitations and concerns highlighted in this review.